Pore Structure and Its Controls of Shale in the Qingshankou Formation, Sanzhao Sag, Songliao Basin - Surong Zhang; Songtao Wu; Rukai Zhu; Jingya Zhang; Chang Liu; Tianshu Zhang; Yi Cai; Mengying Li; Ganlin Hua; Yuan Kang; Bo Wang (Energies, 2023)
The exploration and development of Gulong shale oil in the Songliao Basin has achieved a major breakthrough, with the result that a national shale oil demonstration area is being built. The shale in the Sanzhao Sag is abundant in organic matter and is an important replacement area. For this reason, it has recently become a focus for research and exploration. Compared with the Gulong Sag, the Qingshankou Formation in the Sanzhao Sag is relatively immature, and comparatively little is known about its pore structure. For this study, well ZY1, a key well in the Sanzhao Sag, was selected as the research object. Thin section observation, high-resolution field emission scanning electron microscopy, Modular Automated Processing Systemimaging, X-ray diffraction of whole rock and clay, TOC pyrolysis, and Low-pressure N2 adsorption were used to investigate the pore structure in the sag to determine the factors influencing pore development. The principal understandings are as follows: (1) The Qingshankou Formation in the Sanzhao Sag is predominantly clay shale, with a high content of clay minerals (32.8 to 70%) and TOC contents of 0.7 to 11%. These values indicate good hydrocarbon generation potential. (2) Interparticle pores, intraparticle pores, and organic matter pores are developed. Intergranular pores are the main type, mostly observed between granular minerals or between granular minerals and clays. Intraparticle pores are observed in pyrite mass and dissolved unstable minerals. Organic matter pores (OMP) occur in primary organic matter and migrate into solid bitumen. (3) The shale pores in the Sanzhao Sag are mainly H3-type slit pores, with specific surface areas of 5.4~22.9 m2/g and pore volumes of 0.03~0.07 cm3/g. Mesopores make the largest contribution to pore volume and specific surface area. Scanning electron microscope (MAPS) imaging shows that the pore size distribution of shale is mainly 20~30 nm and 100~200 nm and that large pores, especially pores of 100~200 nm and 1~2 μm, make the largest contribution to the facies. (4) The pore structure in the Sanzhao Sag is affected by mineral composition, abundance of organic matter, thermal evolution degree, and diagenesis. Organic-inorganic interactions influence and determine the pore structure characteristics of the Qingshankou Formation shale. This paper is intended to provide scientific guidance and technical support for evaluating the effectiveness of shale oil reservoirs and selecting sweet spots in the Sanzhao Sag.